2018
DOI: 10.3389/fncom.2018.00104
|View full text |Cite
|
Sign up to set email alerts
|

Highly Heterogeneous Excitatory Connections Require Less Amount of Noise to Sustain Firing Activities in Cortical Networks

Abstract: Cortical networks both in vivo and in vitro sustain asynchronous irregular firings with extremely low frequency. To realize such self-sustained activity in neural network models, balance between excitatory and inhibitory activities is known to be one of the keys. In addition, recent theoretical studies have revealed that another feature commonly observed in cortical networks, i.e., sparse but strong connections and dense weak connections, plays an essential role. The previous studies, however, have not thoroug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Thus, spontaneous activity is said to be produced by stochastic resonance. This model of spontaneous activity has been widely used for clarifying the function of cortical neural networks and further expanded upon (Hiratani et al 2013;Omura et al 2015;Kada et al 2018;Nobukawa et al 2019Nobukawa et al , 2020. For example, a log-normal distribution of EPSPs may enhance learning and memory (Hiratani et al 2013;Omura et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, spontaneous activity is said to be produced by stochastic resonance. This model of spontaneous activity has been widely used for clarifying the function of cortical neural networks and further expanded upon (Hiratani et al 2013;Omura et al 2015;Kada et al 2018;Nobukawa et al 2019Nobukawa et al , 2020. For example, a log-normal distribution of EPSPs may enhance learning and memory (Hiratani et al 2013;Omura et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a log-normal distribution of EPSPs may enhance learning and memory (Hiratani et al 2013;Omura et al 2015). Furthermore, by incorporating the dual nature of complex network structures observed in the cortex (Watanabe et al 2016) into a spiking neural network with a long-tailed EPSP distribution, the spatiotemporally complex neural activity of the real cortex was recently reproduced (Kada et al 2018;Nobukawa et al 2019). Hence, a long-tailed distribution of EPSPs in local cortical networks is an important factor for determining the spatiotemporal characteristics of neural activity and enhancing brain functionality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Kriener et al [31] reported that this spontaneous activity that was induced by the log-normal distribution of EPSPs exhibited a complex behavior with slow temporal transitions between bistable activity states. Recently, Kada et al [32] and Nobukawa et al [33] introduced a spiking neural network with a physiologically observed duality of a complex synaptic connection depending on the magnitude of EPSP. Furthermore, we reproduced the complex spatiotemporal spontaneous activity with multiple states of neural activity [33].…”
mentioning
confidence: 99%